Analysis of the Failure of PLC Master Station Communication and DCS DELTA V ON MOV (Motor Operated Valve) at PT. TRANS-Pasific Petrochemical Indotama - Arik Syaiful Rasid; Affan Bachri; Rahman Arifuddin (Merdeka Malang University, 2020)
The development of technology nowadays is very rapid in various fields especially in industrialization that can support a reliable production process, one of which is a motor operated valve (MOV) which is expected to operate continuously. At PT TPPI, there are 37 motor operated valve that are installed using Modbus communication, which currently has a problem with communication namely blinking (opening and closing for a moment) which sits on the condensate trip pump so the refinery stops which can cause billions of rupiah in losses. With these losses, various tests are carried out so that they can find the cause of the MOV blinking that can increase the depth of the system. Checking or retrieving data based on Ohm’s legal theory, conductors, insulators, induction electric motors, motors ( Motor Operated valve), PLC, DCS and Modbus. Based on this theory. It can determine the resistance, isolator and conductor of the RS485 cable whether it is still good or not, besides that it can also know the ability of MOV, PLC, DCS whether it can still send signals using software modbus. This testing uses a Fluke brand multi meter with type 875 to measure the resistance that the resistance value obtained is greater than the calculation results, for testing isulation resistance using the Kyoritsu brand megger with the 3007A model the value is very good. To check DCS using Dell delta V server type 690 precision, it is found that serial communication cannot be redundant, whereas for checking PLC master station using Dell inspiration 1464 laptop with modscan 32 software, the results obtained PLC A can output signals and PLC B signal intermittent. This research or this analysis can find out MOV blinking caused by cable resistance, PLC master station B and Modbus serial.DOI : https://doi.org/10.26905/jeemecs.v3i2.4163